Incidence of deformity recurrence after surgical treatment of hallux valgus toe - risk factors and prevention - Szeliga, Aleksandra; Książek, Tomasz Karol; Francuziak, Anna Ewelina; Dembicki, Piotr Mikołaj; Kozłowska, Kinga; Borowski, Maciej; Dzieszko, Natalia; Szczepański, Michał; Kalinowska, Weronika; Kulasza, Paulina Sara (Quality in Sport, 2025)
Introduction: Hallux valgus (HV) is a prevalent forefoot deformity, defined by lateral deviation of the great toe and medial displacement of the first metatarsal. When conservative measures fail, surgical correction is often required. Despite numerous refined techniques, postoperative recurrence remains a significant clinical challenge, with rates varying depending on the procedure and patient-specific factors. Aim: This review systematically evaluates the incidence of HV recurrence after surgery, identifies anatomical, radiographic, and procedural risk factors, and assesses strategies to prevent relapse and optimize long-term outcomes. Methods: A comprehensive literature review was conducted using PubMed, Google Scholar, Scopus, and ResearchGate. Results and Conclusion: HV recurrence is influenced by multiple factors, particularly pre- and postoperative radiographic parameters such as hallux valgus angle (HVA), intermetatarsal angle (IMA), and sesamoid position. Effective prevention relies on individualized surgical planning, precise correction of deformities, and structured postoperative management, including physiotherapy and appropriate footwear. Recognizing modifiable risk factors and applying evidence-based strategies can reduce recurrence rates and improve patient satisfaction, highlighting the importance of tailored long-term care in HV management.